2015
DOI: 10.1097/aco.0000000000000161
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischemic preconditioning and outcome

Abstract: RIPC may offer a novel inexpensive and noninvasive therapeutic strategy to alleviate organ injury in the perioperative period. However, adequately powered, large, multicenter clinical studies are necessary to accurately determine whether ischemic conditioning can improve the clinical outcomes of patients at risk for ischemia-reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…In this study, a single tourniquet inflation cycle was performed for five minutes that showed to be sufficient to obtain analgesic effects. Zarbock et al [ 24 ] in a recent publication are questioning the need for intermittent tourniquet.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a single tourniquet inflation cycle was performed for five minutes that showed to be sufficient to obtain analgesic effects. Zarbock et al [ 24 ] in a recent publication are questioning the need for intermittent tourniquet.…”
Section: Discussionmentioning
confidence: 99%
“…21 In the study by Zarbock et al, 10 RIPC increased urinary high mobility group box (HMGB) 1, an endogenous factor that mediates activation of the innate immune response including chemotaxis and proinflammatory cytokine release. For cardiac protection, transient limb ischemia releases a low-molecular-weight (<15-kDa) factor that protects the myocardium against ischemia/reperfusion injury in a mechanism that requires opioid-receptor activation and modification of mitochondrial function via ATP-sensitive potassium channels.…”
mentioning
confidence: 99%